MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA DALAM MENGURAI TEKS BACAAN MELALUI DISKUSI KELOMPOK PADA SISWA KELAS VI - ISIH SUBEKTI (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2022)
This Classroom Action Research aims to improve the learning process to improve Indonesian language learning outcomes in parsing Reading Texts through group discussions for sixth graders at SDN Ngeposari II Kapanewon Semanu, Gunungkidul Regency. This research was conducted from August 2021 to October 2021. Through group discussions by implementing four activity steps: Planning, Implementation, Observation and Reflection. In the second cycle of assessment scores, it was shown that the students' ability in learning Indonesian about parsing reading texts through group discussions was able to increase students' competence in learning Indonesian. It was proven that the second cycle score was 86.87, an increase of 21.41 when compared to the first cycle of 65.46 because the results in the second cycle were already showed a very good improvement and had exceeded the researcher's expectations of 80 with a final score of 86.87, the study was stopped with the criteria of a "good" score. It is expected that colleagues will try to do CAR in order to improve learning. In learning in elementary schools, especially Indonesian language subjects, authorized agencies such as the Regional Biddik Sub-district and other agencies are expected to use the results of this research in the context of developing Indonesian language learning in elementary schools by applying the group discussion learning model. ABSTRAKPenelitian Tindakan Kelas, ini bertujuan untuk memperbaiki proses pembelajaran untuk meningkatkan hasil belajar Bahasa Indonesia dalam mengurai Teks Bacaan melalui diskusi kelompok pada siswa kelas VI di SDN Ngeposari II Kapanewon Semanu Kabupaten Gunungkidul.  Penelitian ini dilaksanakan pada bulan Agustus 2021 sampai dengan Oktober 2021 Melalui diskusi kelompok dengan menerapkan empat langkah kegiatan: Perencanaan, Pelaksanaan, Observasi dan Refleksi.  Dalam skor Penilaian siklus II menunjukkan kemampuan siswa dalam pembelajaran Bahasa Indonesia tentang mengurai teks bacaan melalui diskusi kelompok ternyata mampu meningkatkan kompetensi siswa dalam belajar Bahasa Indonesia terbukti skor siklus II mendapat jumlah 86.87 meningkat 21.41 jika dibanding dengan siklus I sebesar 65.46 karena hasil pada siklus II sudah menunjukan peningkatan yang sangat bagus dan sudah melampaui harapan peneliti sebesar 80 dengan skor akhir 86.87 maka penelitian dihentikan dengan kriteria nilai “Baik”. Diharapkan teman sejawat mau mencoba melakukan PTK dalam rangka perbaikan pembelajaran. Dalam pembelajaran di SD khususnya mata pelajarn Bahasa Indonesia, instansi berwenang seperti Korwil Biddik Kecamatan dan instansi lainnya diharapkan dapat menggunakan hasil penelitian ini dalam rangka pengembangan pembelajaran Bahasa Indonesia di SD dengan penerapan model pembelajaran diskusi kelompok.